ZnO Nanowire Arrays for Enhanced Photocurrent in PbS Quantum Dot Solar Cells. (26th February 2013) - Jean, Joel; Chang, Sehoon; Brown, Patrick R.; Cheng, Jayce J.; Rekemeyer, Paul H.; Bawendi, Moungi G.; Gradečak, Silvija; Bulović, Vladimir
<x xml:space="preserve">Abstract</x> Vertical arrays of ZnO nanowires can decouple light absorption from carrier collection in PbS quantum dot solar cells and increase power conversion efficiencies by 35%. The resulting ordered bulk heterojunction devices achieve short‐circuit current densities in excess of 20 mA cm−2 and efficiencies of up to 4.9%. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>